2021
DOI: 10.1186/s12890-021-01739-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial prescription and the associated factors among outpatients diagnosed with respiratory tract infections in Mbarara Municipality, Uganda

Abstract: Background Respiratory tract infections (RTI) are the second most frequent diagnosis after Malaria amongst Outpatients in Uganda. Majority are Non pneumonia cough and flu which are self-limiting and often do not require antibacterials. However, antibiotics are continuously prescribed for these conditions and are a major contributor to antimicrobial resistance and wastage of health resources. Little is known about this problem in Uganda hence the impetus for the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This highlights the common practice of antibiotic use in managing RTIs. These findings are consistent with those from public health facilities in Mbarara City, Uganda, which reported an antibiotic encounter rate among RTI patients of 77.6% [8].…”
Section: Appropriateness Of Antibiotic Prescriptionsupporting
confidence: 90%
See 1 more Smart Citation
“…This highlights the common practice of antibiotic use in managing RTIs. These findings are consistent with those from public health facilities in Mbarara City, Uganda, which reported an antibiotic encounter rate among RTI patients of 77.6% [8].…”
Section: Appropriateness Of Antibiotic Prescriptionsupporting
confidence: 90%
“…These rates exceeded the acceptable ranges of 0-30% for acute bronchitis and 0-20% for the other RTIs [21]. The rate of antibiotic prescription for acute URTIs was slightly higher than that reported in Mbarara City, Uganda at 68.7% [8], indicating an over-prescription of antibiotics for viral RTIs where they are not required. Comparison with international rates showed that Canada had lower rates for acute bronchitis (52.6%), acute sinusitis (48.4%), and otitis media (39.3%) [28].…”
Section: Appropriateness Of Antibiotic Prescriptionmentioning
confidence: 79%
“… 7 Antibiotics are generally prescribed to patients with respiratory tract infections on a probabilistic basis in most health facilities in sub‐Saharan Africa, and this can lead to antibiotic resistance. 8 , 9 , 10 , 11 Many health systems in sub‐Saharan Africa do not have an effective antimicrobial stewardship program because of the lack of a proper diagnostic technical platform. 12 , 13 Selective use of antimicrobials based on proper diagnosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly identified viruses are influenza, rhinovirus, respiratory syncytial virus, and coronavirus 7 . Antibiotics are generally prescribed to patients with respiratory tract infections on a probabilistic basis in most health facilities in sub‐Saharan Africa, and this can lead to antibiotic resistance 8–11 . Many health systems in sub‐Saharan Africa do not have an effective antimicrobial stewardship program because of the lack of a proper diagnostic technical platform 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that for certain conditions in LMICs, inappropriate prescribing can reach 100% [ 15 ]. A considerable proportion of antibiotics are prescribed inappropriately for acute respiratory tract infections (RTIs), which are essentially viral in origin requiring no antibiotic to aid symptom relief [ 7 , 16 , 17 , 18 , 19 ]. There are a number of factors that influence prescribing behavior.…”
Section: Introductionmentioning
confidence: 99%